Formulasi Media Tanam Berbasis Bahan Lokal dan Inokulasi Mikoriza untuk Peningkatan Pertumbuhan Awal Bibit Coffea arabica - Ali, Fandyka Yufriza (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
The early growth of Coffea arabica seedlings is highly influenced by the quality of the growing medium and nutrient uptake efficiency during the nursery phase. This study aimed to evaluate the effect of local-material-based growing media formulations and arbuscular mycorrhizal fungi (AMF) inoculation on the vegetative growth of C. arabica Lini S 795 seedlings. The experiment was conducted using a completely randomized design (CRD) with eight treatments involving combinations of soil, rice husk, fermented manure, and Glomus sp. mycorrhiza, each replicated three times. Observed parameters included plant height, leaf number, root length, root dry weight, and shoot dry weight. Results showed that the combination of soil, rice husk, manure, and mycorrhiza significantly enhanced all growth parameters compared to the control. The synergistic interaction between local organic components and biological agents improved the physical, chemical, and biological properties of the growing media, thereby optimizing root and shoot development. These findings suggest that integrating locally available organic materials with mycorrhizal inoculants offers an effective, eco-friendly, and sustainable approach to coffee seedling cultivation, with high potential for broader field-scale application.